2019
DOI: 10.1155/2019/5209624
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Mechanical Performance, and Dimensional Stability of Radiata Pine (Pinus radiata D. Don) Scrimbers

Abstract: Natural wood has certain advantages such as good processability and high specific strength and thus has been used for millennium as a structural material. But the mechanical performance and water resistance, particularly for fast-growing species, are unsatisfactory for high-end applications. In this study, the “new-type” scrimber technology was introduced to radiata pine (Pinus radiata D. Don) scrimbers. The structure, mechanical properties, and dimensional stability of the scrimber panels were investigated. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Kumar A et al [20] investigated the mechanical properties of bamboo scrimber and found that the highest modulus and strength properties, when the density is 1.2 g/cm 3 . Wei et al [21] demonstrated that the increase of density was positively related to the increase of the stiffness and strength of bamboo scrimber. The bending strength with density of 0.8 g/cm 3 was 120 MPa, much larger than wood-based panels [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Kumar A et al [20] investigated the mechanical properties of bamboo scrimber and found that the highest modulus and strength properties, when the density is 1.2 g/cm 3 . Wei et al [21] demonstrated that the increase of density was positively related to the increase of the stiffness and strength of bamboo scrimber. The bending strength with density of 0.8 g/cm 3 was 120 MPa, much larger than wood-based panels [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced performance of WS is closely related to the specific structure of WFB, characterized by a controlled cracking pattern where the longitudinal fibers remain intact, and the transverse fibers are partially connected [13], thereby improving permeability and adhesion. Therefore, the quantitative evaluation and online regulation of the cracking degree (CD), such as the use of machine vision and CT [14,15], could help improve and stabilize the quality of WFB.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the specific surface area cannot be directly and effectively measured in practice. Therefore, previous studies have indirectly characterized the CD by soaking the water absorption of WFB in 5-10 min [12,13,18]. Although this method can classify the CD, the non-online grading judgment process can only be used for sampling checks.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the bamboo bundles are separated in situ exhibiting loosened horizontally and continuous longitudinally [7]. Notably, earlier efforts showed that the cracks in bamboo bundles create abundant pathway for adhesive penetration, which developed into water resistance and dimensional stability in bamboo scrimber [10][11][12][13]. For example, the findings by Wei and Li reported that thinner bamboo bundles had a significant benefit of 114% water absorption and 142.3% in the distribution of adhesives, which resulted in 20% and 50% increments in water resistance and mechanical properties of bamboo scrimber, respectively [11,12].…”
Section: Introductionmentioning
confidence: 99%